UKURAN BANK, MANAJEMEN LABA, DAN STABILITAS KEUANGAN BANK - Sutandijo Sutandijo; Listya Sugiyarti (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
This study aims to empirically test and analyze bank company size and earnings management on bank stability with liquidity, BHC (Bank Holding Company), SOE (State Owned Enterprise), and NEW (de novo bank) as control variables. The population in this study is national commercial banks consisting of private banks and state-owned banks registered with the Financial Services Authority (OJK) for the period 2011-2019. By using purposive sampling method, the number of bank companies that were sampled in this study were 57 bank companies with a total of 855 observations of financial statement data with a period of 28 quarters (9 years). In this study used multiple linear regression analysis techniques and Ordinary Least Square model with data processing using eviews 9 software. The results of this study indicate that simultaneously bank size and earnings management, with control variables namely liquidity, BHC, SOE, and NEW have a significant effect on bank stability. Partially the size of bank and NEW have a negative effect on bank stability, liquidity and SOE affect the stability of the bank positively. Meanwhile, bank earnings management and BHC have no effect on bank stability.